Expert opinion on the clinical use of a combination of antihistamines with leukotriene receptor antagonists in the management of allergic rhinitis in Indian settings - S., Manjula; Kumar M., Krishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Various clinical studies have reported that the combination of montelukast and levocetirizine was effective in alleviating residual symptoms and the improvement of quality of life associated with allergic rhinitis. However, there was a dearth of data regarding the prescription practice among clinical practitioners. So, this study aims to gather clinicians’ opinion regarding the use of antihistamines, with a special focus on the combined use of antihistamines with leukotriene receptor antagonists for the management of AR in Indian settings. Methods: The multiple-response questionnaire-based survey involving 19 questions gathered information on current recommendations, clinical observations, clinical experience of specialists in AR management, and the use of montelukast with levocetirizine in routine settings. Results: Out of 388 participants, approximately 84% of respondents preferred a combination of antihistamines and leukotriene receptor antagonists for managing AR. Additionally, 36% stated that 26 to 50% of patients presenting to routine practice may require montelukast and antihistamine combination as treatment. Around 61% endorsed the combination of antihistamines with leukotriene receptor antagonists as the preferred AR treatment strategy. In long-term AR management, 65% of clinicians rated montelukast with levocetirizine as excellent, and 78% of respondents reported montelukast confers additive benefits when combined with antihistamines. Conclusions: The significant preference for the combined use of antihistamines and leukotriene receptor antagonists underscores their perceived efficacy in AR treatment. The combination of antihistamines with leukotriene receptor antagonists emerges as the favored strategy for managing AR.